2 - Reclaiming Mobility: A Pan-Africanist Approach to Migration - Patricia Daley (CODESRIA Bulletin, 2021)
For Africa as a whole we want our peoples to have the right to move, settle, work and live with- out visas or passports from Cape Town to Cairo. As steady progress is being made at regional level it makes this Pan African dimension inevitable ... It just means that they are free to do so if they wish without any security or police always harassing them as ‘foreigners’. (Raheem 2006)